2019
DOI: 10.1186/s13071-019-3493-9
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF mass spectrometry as a diagnostic tool in human and veterinary helminthology: a systematic review

Abstract: Background Matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry (MS) has become a widely used technique for the rapid and accurate identification of bacteria, mycobacteria and certain fungal pathogens in the clinical microbiology laboratory. Thus far, only few attempts have been made to apply the technique in clinical parasitology, particularly regarding helminth identification. Methods We systematically reviewed the scientific litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 167 publications
(88 reference statements)
0
36
0
2
Order By: Relevance
“…Although widely used as a diagnostic tool for accurate identification of bacteria, very few studies have tried to translate the advantages of the MALDI–TOF MS technique to clinical parasitology [ 8 , 9 ], and therefore, as far as we know, there are no related commercially MALDI–TOF MS ID spectral library databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although widely used as a diagnostic tool for accurate identification of bacteria, very few studies have tried to translate the advantages of the MALDI–TOF MS technique to clinical parasitology [ 8 , 9 ], and therefore, as far as we know, there are no related commercially MALDI–TOF MS ID spectral library databases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, three platforms, i.e., MALDI Biotyper (Bruker Daltonics GmbH, Bremen, Germany), VITEK MS (bioMerieux, Marcy-l’Étoile, France), and Andromas MS (Paris, France) are currently approved for routine use and adopted by many clinical microbiological laboratories [ 4 , 5 , 6 , 7 ], facilitating the clinical identification of many pathogenic microorganisms, including bacteria, yeasts, and filamentous fungi. However, an increase of applications of this technology has been observed in the last 10 years, with encouraging results also in studies regarding parasites [ 8 , 9 ]. A recent application of MALDI–TOF MS for Dirofilaria and Ascaris protein-based profiling showed a promising scenario towards clinical applications involving nematodes biotyping [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) has become a widely employed tool for the diagnosis of bacteria and fungi in clinical samples [ 18 , 19 , 20 ]. More recently, a variety of studies have reported the use of MALDI-TOF MS as a potentially promising tool for the identification of mosquitoes [ 21 , 22 ], ticks [ 23 ], and, to a lesser extent, parasites (protozoa and helminths) [ 24 ]. In contrast to PCR-based techniques, MALDI-TOF MS allows for a broad, “untargeted” detection of microorganisms if these are present in the database used for pathogen identification.…”
Section: Introductionmentioning
confidence: 99%
“…In the case report of Tarini et al, the causative agent of meningitis for a 50-year-old male patient was identified as S. mitis with a 99% probability (based on the VITEK 2 Compact ID/AST system), while sequencing results from cerebrospinal fluid confirmed S. suis as the true pathogen [ 99 ]. The increasing use of modern diagnostic tools (e.g., PCR, MALDI-TOF MS) and methods available for use directly from clinical specimens may further aid the identification biochemically inactive or unreliably-identified isolates [ 100 , 101 ]. A very recently published report by Olearo et al showed the first imported human case of S. suis infection in Switzerland: a 45-year-old woman bought and consumed raw pork meat imported from a small local farm in Moldova 24 h before flying back to Geneva, Switzerland.…”
Section: Discussionmentioning
confidence: 99%